1994
DOI: 10.1108/09578239410062914
|View full text |Cite
|
Sign up to set email alerts
|

Education Reforms and Professional Development of Principals: Implications for Universities

Abstract: The current thrust towards devolution of power to schools has altered and expanded the principal′s role. Principals are being made responsible for school review and planning, local selection of staff, school‐based staff development, performance appraisal, financial management, and the establishment of school councils. Principals need professional development to cope successfully with these new requirements. Reviews the immediate administrative training needs of school leaders, and then examines the dilemma uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
0
6
0
1
Order By: Relevance
“…Under this ideological pressure, leadership development programmes in education have given priority to academic traditionalist objectives which prioritise the development of managerial skills alongside knowledge and understandings that serve pragmatic problem solving. In so doing, leadership development appears to be decontextualised and privileging theory in the face of the situational, contextual, and experiential realities of leadership practice (Begley, 2001;Brundrett, 2001;Bush, 1999;Cardno, 2003;Creissen and Ellison, 1998;Johnson, 1994;Millken, 2002). Affective and dispositional concerns are antithetical to the neoliberal ideology (Begley, 2001(Begley, , 2003(Begley, , 2006Bhindi and Duignan, 1997;Luckock, 2007;Starratt, 2007;Walker and Shuangye, 2007).…”
Section: An Educationally Relevant Programme 231mentioning
confidence: 99%
See 1 more Smart Citation
“…Under this ideological pressure, leadership development programmes in education have given priority to academic traditionalist objectives which prioritise the development of managerial skills alongside knowledge and understandings that serve pragmatic problem solving. In so doing, leadership development appears to be decontextualised and privileging theory in the face of the situational, contextual, and experiential realities of leadership practice (Begley, 2001;Brundrett, 2001;Bush, 1999;Cardno, 2003;Creissen and Ellison, 1998;Johnson, 1994;Millken, 2002). Affective and dispositional concerns are antithetical to the neoliberal ideology (Begley, 2001(Begley, , 2003(Begley, , 2006Bhindi and Duignan, 1997;Luckock, 2007;Starratt, 2007;Walker and Shuangye, 2007).…”
Section: An Educationally Relevant Programme 231mentioning
confidence: 99%
“…The privileging of skill development and rationalist argument occur at the expense of other critical, holistic and experiential approaches ( Johnson, 1994;Restine, 1997;Shor, 1992;Southworth, 1995). As such, the predominant ideological discourse continues to be legitimated and systemically persistent (Barnett, 2003;Giroux, 1981;Meighan and Siraj-Blatchford, 2003).…”
Section: An Educationally Relevant Programme 231mentioning
confidence: 99%
“…The curricula of many school leadership programs have begun to focus on the inclusion of more learning experiences directed toward helping future school leaders recognize the need to oversee the teaching-learning activities in their schools as their primary area of attention and responsibility (Barnett, 1992;Bratlien, 1992;Paull, 1995). The instructional leaders also need to enable and support teacher success (Clark and Clark, 1996;Johnson, 1994); empower others to create collaboration and open communication (Bratlien, 1992); encourage risk taking and provide leadership in curriculum renewal (Bratlien, 1992); and diagnose student needs, monitor student achievement, and promote collaboration by working with faculty and encouraging student/parent input (Bratlien, 1992). However, research conducted by Hsieh and Shen (1998) indicated that from teachers to principals and to superintendents, their conception ofleadership gradually moves from instructional to political matters.…”
Section: Instructional Leadershipmentioning
confidence: 99%
“…Colleges and universities face a quandary of whether to focus on theory (a traditional strength of higher education) or on practical knowledge and skills (Dunklee, 2000;Johnson, 1992;Muse & Thomas, 1991). Murphy (2001) states:…”
Section: Lacking Adequate Preparationmentioning
confidence: 99%
“…According to Johnson (1992), it is the major responsibility of universities to develop educational leadership programs that encompass the type of theoretical and practical preparation needed to meet new and changing responsibilities. Flanary (2000) states, "It's one thing to have the book knowledge of what it means to lead a school, but it's quite another to step into a school with 500 to 5,000 students and be able to put that knowledge into action" (p. 3).…”
Section: Lacking Adequate Preparationmentioning
confidence: 99%